Stages of Change: Moving Community Pharmacies From a Drug Dispensing to Population Health Management Model. (February 2021) - Turner, Kea; Weinberger, Morris; Renfro, Chelsea; Powell, Byron J.; Ferreri, Stefanie; Trodgon, Justin G.; Mark, Nicole; Trygstad, Troy; Shea, Christopher M.
Given their clinical training and accessibility, community pharmacists are well positioned to support primary care, especially in providing medication management services. There is limited evidence, however, on implementation of community pharmacist-led services in coordination with other health care providers. The aim of this study was to examine the implementation process of community pharmacies in North Carolina participating in a Medicaid population health management intervention. We conducted semistructured interviews with 40 representatives from high- and low-performing community pharmacies from June to August 2017. We analyzed for themes organized around Rogers's Stages in the Innovation Process in Organizations. Community pharmacies employed numerous implementation strategies such as developing relationships with providers and redefining job responsibilities to ensure pharmacists and pharmacy technicians are working at the top of their license. Findings also revealed differences in the implementation process among high- and low-performing pharmacies. Continued research is needed to determine which implementation strategies improve program performance.